Smart stimuli-responsive hydrogels for drug delivery in periodontitis treatment - Wang, Yuxiao; Li, Jiaxin; Tang, Maomao; Peng, Chengjun; Wang, Guichun; Wang, Jingjing; Wang, Xinrui; Chang, Xiangwei; Guo, Jian; Gui, Shuangying (Biomedicine & pharmacotherapy, 2023)
Periodontitis is a chronic inflammatory disease initiated by pathogenic biofilms and host immunity that damages tooth-supporting tissues, including the gingiva, periodontal ligament and alveolar bone. The physiological functions of the oral cavity, such as saliva secretion and chewing, greatly reduce the residence of therapeutic drugs in the area of a periodontal lesion. In addition, complex and diverse pathogenic mechanisms make effectively treating periodontitis difficult. Therefore, designing advanced local drug delivery systems and rational therapeutic strategies are the basis for successful periodontitis treatment. Hydrogels have attracted considerable interest in the field of periodontitis treatment due to their biocompatibility, biodegradability and convenient administration to the periodontal pocket. In recent years, the focus of hydrogel research has shifted to smart stimuli-responsive hydrogels, which can undergo flexible sol-gel transitions in situ and control drug release in response to stimulation by temperature, light, pH, ROS, glucose, or enzymes. In this review, we systematically introduce the development and rational design of emerging smart stimuli-responsive hydrogels for periodontitis treatment. We also discuss the state-of-the-art therapeutic strategies of smart hydrogels based on the pathogenesis of periodontitis. Additionally, the challenges and future research directions of smart hydrogels for periodontitis treatment are discussed from the perspective of developing efficient hydrogel delivery systems and potential clinical applications. [Display omitted] •Smart stimuli-responsive hydrogels can respond to external stimuli to periodontitis treatment.•Smart stimuli-responsive hydrogels allow triggered transitions between solution and solid in the periodontal pocket.•Smart stimuli-responsive hydrogels with switchable and controlled drug release properties can be tailored.•Review the development and rational design of emerging smart stimuli-responsive hydrogels for periodontitis treatment.•Discuss the latest therapeutic strategies of smart hydrogels based on the pathogenesis of periodontitis.